Microbiological Analysis of Stored Groundnuts in Yenagoa, Bayelsa State, with Emphasis on Aflatoxin-Producing Aspergillus Species - Akpomedaye, Salvage (Kwaghe International Journal of Sciences and Technology, 2025)
Groundnuts (Arachis hypogaea), an important dietary protein source and economic crop in Nigeria, are highly susceptible to fungal contamination during storage, particularly by Aspergillus species that produce aflatoxins. Aflatoxin B₁, the most potent of these toxins, is a Group 1 carcinogen associated with liver cancer, immune suppression, and growth retardation. Despite the widespread consumption of groundnuts in Yenagoa, Bayelsa State, limited data exist on microbial and aflatoxigenic contamination in the local supply chain. This study assessed the microbiological quality of stored groundnuts with emphasis on aflatoxin-producing Aspergillus species across three major markets—Swali, Opolo, and Tombia. Thirty samples (10 per market) were analyzed using serial dilution, culturing on Potato Dextrose Agar (PDA) and Aspergillus flavus and parasiticus agar (AFPA), and microscopic identification with lactophenol cotton blue staining. Aflatoxin production was screened qualitatively using the Ammonia Vapor Test, and moisture content was determined by the oven-dry method. Results showed that 80% of samples were contaminated with Aspergillus spp., predominantly A. flavus (50%) and A. parasiticus (23.3%). Aflatoxin detection was 60% overall, highest in Tombia (70%), followed by Swali (60%) and Opolo (50%). Tombia samples also recorded the highest mean moisture content (11.1%), exceeding the safe threshold (<8%) for fungal inhibition. Additional fungi, including Penicillium, Fusarium, and Rhizopus spp., were also isolated, indicating poor storage hygiene. These findings underscore a serious food safety concern in Yenagoa, where high aflatoxigenic fungal prevalence, driven by elevated moisture and inadequate storage, poses significant health risks. The study recommends routine surveillance, vendor education, and affordable moisture-proof storage interventions to reduce aflatoxin exposure and protect public health in Bayelsa and similar tropical contexts.